Free-space optical channel performance under atmospheric losses using orthogonal frequency division multiplexing - Mani, Vinoth Kumar; Kumar, Vinod (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Free space optics (FSO) is a fast-growing technology that outperforms fiber optics in communication network infrastructure without spectrum licensing. The goal of this work is to evaluate the performance of the FSO communication system using direct detection 4-quadrature amplitude modulation (4-QAM) and 4-phase shift keying (4-PSK) with orthogonal frequency division multiplexing (OFDM) scheme. Simulating a direct detection OFDM-FSO system and comparing constellation diagrams, electrical power, and optical power have been used to conduct the analysis. The model is validated using a constellation diagram of received signals for various FSO channel ranges and weather conditions. According to simulation results, the OFDM-FSO architecture combined with the 4-QAM modulation technique produces the most efficient output with the least amount of power consumption for data rates up to 10 Gb/s and FSO channel ranges of up to 3 km for clear air, 1.7 km, and 1.3 km for thin and thick fog, and 0.7 km for heavy fog. This investigation can enhance the current fiber optic network's structure connected with the FSO system to provide last-mile connectivity in 5G modules.